New words - Hargraves, Orin (Oxford University Press, 2004)
Oxford lexicographers dive into the sea of language to catch these words as soon as they hatch; then they set about defining these additions to English, which may come from slang, other languages, technical jargon, or scientific breakthroughs. Oxford's rigorous standards result in definitions with the precision and accuracy that readers expect from the most trusted name in reference